122k views
2 votes
helpppppppppppppppppppppppppppppp meeeeeeeeeeeeeeeeeee plsssssssssssssssssssssss there is more but plss help mee​

helpppppppppppppppppppppppppppppp meeeeeeeeeeeeeeeeeee plsssssssssssssssssssssss there-example-1

1 Answer

4 votes

Answer: The attachment is a bit difficult to read, and long. I'll make some suggestions and add some detail to a few of the problems, but would ask that these suggestions be applied to other problems to find the answers.

Explanation:

9. Coinciding lines line on top of each other. I.e., they are the same equation. If we take A, for example, we can reduce the second expression by dividing by 2: (2x+4y=6)/2 = (x + 2y = 3). This matches the first expression (x + 2y = 3). ! Whoa, that went fast.

10. (x+8)(x-8) = x² +8x -8x - 64 = x² - 64

11. I don't have the time to explain how one can factor, but practice is important. And I don't know if this is completely factored, but it matches one of the options. Try (n-2)(n²+2n + 4) [n³ +2n² +4n - 2n² -4n -8 = n³ - 8. It works.

12. The denominators are the same, so add the numerators and keep the denominator. (7x+4y)/x²y

13. The slope is the "Rise" over the "Run." (3,4), (8,-1) Rise = (-1 - 4) = -5. Run = (8-3) = 5 Slope = -(5/5) = -1

14. A line with a positive slope will move upwards as x increases. We can eliminate options C and D immediately. That leaves A and B. The line we are looking for is y = 5x + b. We are not given b, the y-intercept, so determine the slopes of both lines: I get 4 for A and 5 for B. To confirm B is correct, we could calculate b for y=5x+b by using given point, (2,3). 3 = 5*2 + b, b = -7. We can't see this point (0,-7) on the graph, but it appears correct. B is the best answer.

15. The line will have the form of y=mx+b. Calculate m, the slope, from the two points (3,1) and (4,7). Rise = 6, Run = 1 Slope = 6. y=6x+b. Find b by using either of the given poins and solving for b. I'll choose (3,1). y=6x+b; 1 = 18 + b; b = -17. The equation is y=6x-17. Rearrange option A (y =6x - 17).

16. The second value in each factor must, when multiplied together, equal the final term of the original expression, -9y². I see only one option for which that is true, C. Multiply the two factors in C to be certain, and you'll find they result in the correct expression.

User Rimraf
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.